1989
DOI: 10.1073/pnas.86.20.7952
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Kearns-Sayre/chronic external ophthalmoplegia plus syndrome associated with a mitochondrial DNA deletion: a slip-replication model and metabolic therapy.

Abstract: The muscle mitochondria of a patient with Kearns-Sayre/chronic external ophthalmoplegia plus syndrome were found to be completely deficient in respiratory complex I activity and partially deficient in complex IV and V activities. Treatment of the patient with coenzyme Q10 and succinate resulted in clinical improvement of respiratory function, consistent with the respiratory deficiencies. Restriction enzyme analysis of the muscle mtDNA revealed a 4.9-kilobase deletion in 50% of the mtDNA molecules. Polymerase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
237
0
3

Year Published

1991
1991
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 448 publications
(243 citation statements)
references
References 31 publications
(44 reference statements)
3
237
0
3
Order By: Relevance
“…Current hypotheses are based on properties of previously observed deleted mtDNA molecules. The fact that deletions have often been observed in the major arc between the two replication origins of the mitochondrial genome lead to the assumption that slipped-strand replication is one of the main sources of mtDNA deletion generation (68). Replication can, however, also play a role in deletion formation through inducing double-strand breaks (DSBs).…”
Section: Genetic Mechanisms Explaining Disease Progressionmentioning
confidence: 99%
“…Current hypotheses are based on properties of previously observed deleted mtDNA molecules. The fact that deletions have often been observed in the major arc between the two replication origins of the mitochondrial genome lead to the assumption that slipped-strand replication is one of the main sources of mtDNA deletion generation (68). Replication can, however, also play a role in deletion formation through inducing double-strand breaks (DSBs).…”
Section: Genetic Mechanisms Explaining Disease Progressionmentioning
confidence: 99%
“…These studies found several large-scale deletions of mtDNA in photoaged skin. To explain the generation of these largescale deletions in mtDNA, a modified slip-replication mechanism and a central role of ROS have been postulated (39)(40)(41). Recent work has been able to provide a possible link for the involvement of ROS in the generation of the most frequent mtDNA deletion, the so-called common deletion (42).…”
Section: Mitochondrial Dnamentioning
confidence: 99%
“…These modified bases are especially prone to mispairing of repetitive elements and are correlated with deletions (Lezza et al, 1999). This observation has led to the proposal that deletions are induced via mispairing and slippage during replication (Shoffner et al, 1989). Nowadays it is quite clear that large-scale deletions may be attributed to polymerase slippage, homologous recombination, double strand breaks, inefficient repair mechanisms, or mutations in the helicase twinkle (Zeviani et al, 2003, Phadnis et al, 2005Srivastava and Moraes, 2005).…”
Section: Introductionmentioning
confidence: 99%